1972
DOI: 10.1152/ajplegacy.1972.223.5.1068
|View full text |Cite
|
Sign up to set email alerts
|

Arrhythmias induced by local cardiac nerve stimulation

Abstract: Arrythmias induced by local cardiac nerve stimulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

1982
1982
2013
2013

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(41 citation statements)
references
References 8 publications
3
37
0
Order By: Relevance
“…This is in line with results during epicardial stimulation of the ventrolateral nerve in dogs. 22 The septum also contributes to right ventricular function, and right ventricular pressure did not change during SNS; these findings may be taken as evidence for a different sympathetic neural input to the right ventricle and septum. In accordance with this, other authors have demonstrated that the right ventricular lateral wall is innervated mainly by sympathetic fibers crossing the right atrioventricular groove laterally, whereas the septum receives inputs from nerve fibers that cross the lateral right atrioventricular groove and from fibers coursing alongside the left anterior descending coronary artery.…”
Section: Discussionmentioning
confidence: 77%
“…This is in line with results during epicardial stimulation of the ventrolateral nerve in dogs. 22 The septum also contributes to right ventricular function, and right ventricular pressure did not change during SNS; these findings may be taken as evidence for a different sympathetic neural input to the right ventricle and septum. In accordance with this, other authors have demonstrated that the right ventricular lateral wall is innervated mainly by sympathetic fibers crossing the right atrioventricular groove laterally, whereas the septum receives inputs from nerve fibers that cross the lateral right atrioventricular groove and from fibers coursing alongside the left anterior descending coronary artery.…”
Section: Discussionmentioning
confidence: 77%
“…Experimental and developmental studies of the autonomic cardiac nervous system have also been conducted in animals such as the mouse, rat, rabbit, chick, and dog (Armour et al, 1972;Benítez et al, 1959;Brack et al, 2011;Gomez, 1958;Haws and Burgess, 1978;Hildreth et al, 2008Hildreth et al, , 2009Kirby et al, 1980;Kuratani et al, 1991;Kuratani and Tanaka, 1990;Levy et al, 1966;Mabe and Hoover, 2011;Meyer et al, 2010;Mizeres, 1955Mizeres, , 1957Mizeres, , 1958Mizuno et al, 2010;Oliveira et al, 2010;Roberts, 1991;Schwartz, 2010;Scherlag et al, 2011;Shaner, 1930;Shoba and Tay, 2000;Uchida et al, 2010;Verberne et al, 1998). However, huge differences in the cardiac nervous system between humans and the experimental animals have been recognized (Batulevicius et al, 2003;Brugnaro et al, 2003;Kawashima, 2011;McKibben and Getty, 1968;Rysevaite et al, 2011;Pauza et al, 2002a,b).…”
Section: Introductionmentioning
confidence: 99%
“…Early basic studies showed the relationship between the ICANS and cardiac arrhythmias. 39,40 Anatomy of ICANS Armour et al 41 provided a comprehensive anatomic study of the ICANS in the human heart by delineating the locations of the major ganglionated plexi and their axonal fields and peripheral ganglia. This study demonstrated that the ICANS is "distributed more extensively than previously considered."…”
Section: Intrinsic Cardiac Autonomic Nervous Systemmentioning
confidence: 99%